Design and development of tractor operated onion set planter - A CAROLIN RATHINAKUMARI; D MANOHAR JESUDAS (The Indian Journal of Agricultural Sciences, 2015)
The paper describes the design and development of planter for planting onion sets of aggregatum group onions Onion (Allium cepa L.) in close-spacing. The onion set planter developed consisted of onion set planting unit, seed hopper, standard three point hitch for mounting to tractor, main frame, furrow opener, ground wheel, and drive transmission mechanism. The onion set planter was evaluated in the laboratory for its performance. The performance indices namely multiple index, miss index, quality of feed index, precision, mean and standard deviation of onion set planter were 0.05, 0.18, 0.77, 0.27, 11.71 and 5.22 cm’ respectively. The precision of 0.27 was in the acceptable region for indicating the encouraging performance of planter in terms of planting single sets. The tractor operated onion set planter was tested in the field for its performance. The onion sets were graded into four grades. All the four grades of the onion sets were planted by the prototype onion set planter. Plant to plant spacings were 9.34±1.530, 10.35±2.162, 11.50±2.305 and 12.64±2.758 cm for the grades I(2-3 g weight), II(3-4 g weight), III(4-5 g weight) and IV(5-6 g weight) on 12 DAP respectivety. The field capacity of the onion set planter was 0.15 ha./h. The cost of operation was Rs.` 4 150/ha. The cost saved by using onion planter over manual planting was about 30%.